Melanoma in Dogs in the Backlands of Northeastern Brazil - Epidemiology, Risk Factors and Clinicopathological Findings - Lopes de Lima, André; Platini Ferreira de Souto, Erick; Norberto de Oliveira, Lucas; dos Santos Carneiro, Rosileide; Noronha de Toledo, Gabriela; José Nogueira de Galiza, Glauco; Medeiros Dantas, Antonio Flávio (Acta Scientiae Veterinariae, 2022)
Background: Melanoma is a malignant neoplasm that arises from melanocytes and malanoblasts. It is also more frequently reported in dogs than in other species. They may arise from melanocytes in the skin, on the surfaces of the mucous membranes, and eyes. The aim of this study was to describe the epidemiological aspects, risk factors and clinicopathological findings of melanoma in dogs in the backlands, northeastern Brazil. Materials, Methods & Results: A retrospective study was carried out in all biopsy samples and necropsy examinations of dogs, from January 2003 to December 2021, at the Animal Pathology Laboratory of the Federal University of Campina Grande, Patos, Paraiba, northeastern Brazil. Epidemiological data, clinical signs, and gross lesions were reviewed from the diagnostic laboratory reports. Samples of the skin, lymph nodes, central nervous system and organs of the thoracic and abdominal cavities were fixed in 10% buffered formalin, processed routinely for histopathology, embedded in paraffin wax, cut into 4 µm sections, and stained with hematoxylin and eosin (HE). Histological sections were also submitted to immunohistochemistry with the primary antibody anti-Melan A. Of the 4717 records found, 1158 (24.5%) were diagnosed with neoplasms, of which 48 (4.14%) cases were of melanoma. Of this total, 28 (58.3%) dogs were elderly, 19 (39.6%) were adults, and 1 (2.1%) was young. Mixed breed animals were the most affected (42.6%), followed by the pinscher breed (19.1%). According to the anatomical region, the most affected site was the skin (38/53=71.7%), followed by the oral cavity (12/53=22.65%) and the eyes (3/53=5.7%). Grossly, the skin lesions were characterized by exophytic and usually blackened, sometimes irregular and firm, nodules. At cut, they had a smooth, compact and blackened surface. Lesions in the oral cavity were characterized by blackened, irregular and infiltrating nodules or masses. The ocular lesions were always unilateral and were characterized by an enlarged and diffusely blackened eyeball, with areas of ulceration and subversion of tissue architecture. In 5 animals there was more than one anatomical site affected, totaling 53 lesions. In 9 (17%) cases, metastases were identified, 8 in regional lymph nodes and 1 in the lung. Histopathology showed a densely non-encapsulated, poorly delimited, expansive and infiltrative neoplasm, composed of neoplastic cells arranged in islands or nests and supported by fibrovascular stroma, containing a variable amount of brownish pigment (melanin). Immunohistochemistry showed strong immunostaining of the neoplastic cells in brown by the anti-Melan A antibody. Discussion: The diagnosis of melanoma was established based on epidemiological, clinical, anatomopathological, and immunohistochemical findings. Gender is not a predisposing factor, and although there was no statistically significant relationship, males were more affected. Senescence is a conditioning risk factor. Elderly animals were more affected (P < 0.0001) than adult ones, with OR = 4.38; and young ones (P = 0.0051), with OR = 12.65. Some breeds, especially those with marked skin pigmentation, were more affected, however the most affected ones in this survey were pinscher and poodle. Cutaneous melanoma accounted for almost 72% of cases, contesting recent studies where oral cavity melanoma was more frequent. Therefore, it is believed that the climatic conditions of the backlands sub-region, in northeastern Brazil, associated with the individual characteristics of the dogs, are involved in the development of these neoplasms, since the climate is predominantly dry, with high temperatures throughout the year, with maximums that can reach 40ºC, favoring the exposure to high incidence of ultraviolet radiation. Keywords: dog disease, dermatopathy, neoplasm, melanocytes. Título: Melanomas em cães no Sertão do Nordeste do Brasil - epidemiologia, fatores de risco e achados clinicopatológicos Descritores: doença de cão, dermatopatia, neoplasma, melanócitos.